2019
DOI: 10.1093/heapol/czz118
|View full text |Cite
|
Sign up to set email alerts
|

Energy access in Malawian healthcare facilities: consequences for health service delivery and environmental health conditions

Abstract: Many healthcare facilities (HCFs) in low-income countries experience unreliable connectivity to energy sources, which adversely impacts the quality of health service delivery and provision of adequate environmental health services. This assessment explores the status and consequences of energy access through interviews and surveys with administrators and healthcare workers from 44 HCFs (central hospitals, district hospitals, health centres and health posts) in Malawi. Most HCFs are connected to the electrical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The importance of these alternate power sources in improving the health services is therefore reinforced from our findings. However, the use of diesel generators (DGs) at these rural health facilities presents its own set of challenges [ 11 ]. DGs pollute the local environment, produce a lot of noise which affects the care environment, they break down regularly, repairs take time, and in remote centers, the very procurement and storage of adequate quantities of fuel on a regular basis is a challenging task [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of these alternate power sources in improving the health services is therefore reinforced from our findings. However, the use of diesel generators (DGs) at these rural health facilities presents its own set of challenges [ 11 ]. DGs pollute the local environment, produce a lot of noise which affects the care environment, they break down regularly, repairs take time, and in remote centers, the very procurement and storage of adequate quantities of fuel on a regular basis is a challenging task [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of these facilities had medical equipment but no electricity to power them. A qualitative study of Malawian health facilities showed poor electricity access being associated with irregular water supply, poor sterilization, and poor working conditions [ 10 , 11 ]. Another recent report provides a descriptive study of the availability of electricity at Primary Health Centers (PHCs) in India [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The HCFs were located in the Northern, Central, and Southern regions, and the sample comprised central hospitals, district hospitals, and health centers (Table 1). The sampling of HCFs and the development and application of the survey instruments are described in McCord et al, 2019 andReuland et al, 2019. Briefly, facilities were selected to ensure geographical representation and to provide insight into regional variation.…”
Section: Methodsmentioning
confidence: 99%
“…Within medical disciplines, "standard precautions" and "infection control and prevention" include practices for hand hygiene, protective equipment use, waste handling, and cleaning designed to protect patients and providers [44]. Furthermore, many EHS depend on systems which have no direct environmental outputs, but are essential for routine EHS operation, such as the requirement for power and electricity to operate infrastructure [45].…”
Section: Defining Target Outcomes Target Facilities and Timeframesmentioning
confidence: 99%